2015
DOI: 10.1017/s0263034615000944
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of runaway electron inception and breakdown in nanosecond pulse gas discharges

Abstract: Nanosecond pulse discharges can provide high reduced electric field for exciting high-energy electrons, and the ultrafast rising time of the applied pulse can effectively suppress the generation of spark streamer and produce homogeneous discharges preionized by runaway electrons in atmospheric-pressure air. In this paper, the electrostatic field in a tube-plate electrodes gap is calculated using a calculation software. Furthermore, a simple physical model of nanosecond pulse discharges is established to invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 33 publications
1
10
0
1
Order By: Relevance
“…A detailed description of spatial discharge forms and their sequence is presented below. From the data reported here and in other studies [3, 7, 8, 19–22, 25, 28, 30, 48, 49] it follows that it is the runaway electrons which provide preionisation of the discharge gap and formation of a REP DD.…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…A detailed description of spatial discharge forms and their sequence is presented below. From the data reported here and in other studies [3, 7, 8, 19–22, 25, 28, 30, 48, 49] it follows that it is the runaway electrons which provide preionisation of the discharge gap and formation of a REP DD.…”
Section: Resultssupporting
confidence: 76%
“…As has been shown in many papers, diffuse discharges in an inhomogeneous electric field can be formed in different gases at atmospheric and higher pressure whatever the polarity of an electrode with a small curvature radius, see books [3, 40], reviews [7, 8] and papers [19–21, 25–30, 48–54]. In this paper, we consider data on diffuse discharges which occur with SAEB generation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, diffuse gas discharges initiated by runaway electrons (runaway electron preionized diffuse discharge-REP DD) are intensively investigated [1][2][3][4]. As it was shown in [5], it is possible to form a diffuse discharge in a gap with an inhomogeneous electric field strength distribution filled with atmospheric-pressure air by applying nanosecond voltage pulses with an amplitude up to several tens of kilovolts to the cathode with a small radius of curvature.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the amplitude of a runway electron beam current realised in SF 6 with a tubular cathode of 6 mm in diameter at the voltage rise time of ∼2 ns increased considerably as the gap width was decreased from 12 to 8 mm [32]. Reasoning that the beam amplitude is determined by the voltage across the gap, all other things being equal, at the instant of generation of runaway electrons [1–27], it can be assumed that a decrease in the electrode spacing increased the gap voltage [32]. The assumption is indirectly supported by research data on a runaway electron beam produced in nitrogen with the gap of 12 mm and tubular cathode with the diameter of 6 mm at the voltage rise time of 0.3 ns [33], showing a considerable increase in the voltage across the gap and the beam current amplitude with a decrease in the pressure.…”
Section: Introductionmentioning
confidence: 99%